Eco-friendly construction materials and health benefits in the design of an all-inclusive health resorts, Nigeria - Ekhaese, Eghosa N.; Ndimako, Onyedikachukwu O. (Frontiers in Built Environment, 2023)
Health resort designs are health sanctuaries and a conducive treatment, healing, and wellness environment. In providing a health and wellness-beneficial environment, the material selection choices by health resort designers should conform to certain minimum specifications and standards. On this premise and SDG-based selection criteria, the study aims to investigate eco-friendly construction materials and their health benefits in an all-inclusive health resort design proposed for Port Harcourt, Nigeria. This study addressed three key objectives – Ascertaining the physical architectural features of health resorts, assessing the eco-friendly building material contribution to SDG attainment, and identifying the health benefits of eco-friendly building materials in the health resort. The researchers engaged the qualitative research method for the study. While, using a case study technique as a qualitative research design/strategy. The authors used three health resorts across three countries in the global south; China, India, and Brazil. The data collection instruments include; an in-depth interview guide (IDI), a direct observation guide, a checklist of green construction materials for health facilities and a qualitative photo-production study based on the essential features of a health resort checklist. The authors use content and narrative analyses to analyze data. Findings show that eco-friendly materials may be best suited for both exterior and interior works of health resort facilities. Wood, stone and concrete are the most preferred materials as they occur across all three case studies. The results align with current global trends towards eco-beneficial facilities. Adopting natural materials such as wood and stone for the Port Harcourt health resort would be expedient, given the health benefits inherent in using such eco-friendly materials and their alignment with the Sustainable Development Goals (SGD 11 and 13).